(untitled) (Contemporary Journal of Social Science Review, 2025)
This study investigates The Adventures of Sherlock Holmes through a computational literary stylistic approach using Voyant Tools, demonstrating how digital text analysis can deepen and extend traditional literary interpretation. The research aims to uncover the lexical, semantic, and contextual structures that shape Arthur Conan Doyle’s narrative technique and characterize Sherlock Holmes’s detective logic. By employing a mixed-method design integrating quantitative digital outputs with qualitative literary interpretation, the study moves beyond conventional close reading and provides a data-driven understanding of Doyle’s stylistic patterns. The complete digital text of the twelve original stories was uploaded into Voyant Tools, which generated frequency lists, collocation networks, trend graphs, and word clouds. These outputs were systematically analyzed to examine how recurring linguistic patterns construct meaning, reveal character psychology, and reinforce thematic coherence. The results show that Doyle’s prose exhibits a moderate vocabulary density, a dialogic narrative structure, and a strong reliance on repeated investigative terms. High-frequency words such as “Holmes,” “Said,” “Man,” “Know,” and “Think” highlight the detective’s centrality, the dominance of spoken reasoning, and the intellectual focus of the narratives. Semantic patterns link cognitive verbs with sensory imagery such as “Eyes,” “Face,” and “Hand” etc, reflecting Holmes’s method of transforming visual clues into logical deductions. Contextual and trend analyses further reveal rhythmic alternations between dialogue-heavy investigation scenes and quieter deductive moments, illustrating Doyle’s controlled pacing. Collocational structures such as “Said Holmes” and “Mr. Holmes” reinforce Holmes’s authority as the narrative’s rational and moral anchor. Overall, the study demonstrates that computational stylistic analysis provides measurable insights into Doyle’s narrative precision, character construction, and thematic design. By integrating digital linguistics with literary criticism, the research highlights the value of digital humanities in expanding interpretive possibilities and offering a systematic, replicable method for analyzing classic literature. The findings confirm that digital tools like Voyant can uncover hidden textual patterns, enrich literary understanding, and contribute to evolving interdisciplinary research.